Simulating the impact of climate change on energy consumption and yield in Canadian greenhouse horticulture - Marie-Pier Trépanier; Pierre-Olivier Schwarz; Louis Gosselin (Sustainable Futures)
Greenhouse horticulture is a very energy-intensive industry in cold regions such as Canada due to heating and lighting needs. It is still largely unknown how climate change will impact the energy profile and productivity of this vital industry. In this work, a greenhouse producing tomatoes has been simulated in eight Canadian cities under current and 2080 climates based on climatic trajectory RCP8.5, in order to determine how the energy consumption and tomato yield would be affected. Results show that, on average, energy consumption decreases by 11 % due to a reduction of the heating needs, whereas yield decreases by 17 % due to a higher canopy temperature. The use of light-emitting diodes (LED) resulted in a lower energy consumption than that of high-pressure sodium (HPS) lighting in both current and future weather conditions. This work suggests that the greenhouse industry is likely to require some adaptations to climate change and that reaching a balance between energy consumption and productivity will be a challenge. As an example, the addition of a mechanical cooling and dehumidification system was simulated and allowed to increase the yield compared to the current situation, even in the 2080 climate change scenario, at the expense of higher energy consumption. However, a more in-depth analysis is required to identify the best adaptative strategies for mitigating the impacts of climate change on greenhouse production.